Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write (TWT) Terhadap Kemampuan Komunikasi Matematis Siswa Di SMAN 1 Kuok - Dari, Yuni Wulan; Hidayati, Adityawarman; Zulfah (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This research is motivated by the low mathematical communication skills of class X students of SMA Negeri 1 Kuok which can be seen in the learning outcomes of class X students of SMA Negeri 1 Kuok. This study aims to determine whether or not there is an influence of the Think Talk Write cooperative learning model on the mathematical communication skills of class X students of SMA Negeri 1 Kuok. This research is a quasi-experimental study, with a sample technique used simple random sampling. The population in this study were class X students of SMA Negeri 1 Kuok in the 2024/2025 Academic Year consisting of 2 classes. The samples in this study were class X.1 as the control class and class X.2 as the experimental class. The instruments used in this study were learning implementation sheets and mathematical communication ability test questions. The data analysis technique used was the Independent sample T-Test and the N-Gain test with the help of SPSS 25 software. The results of the Independent sample T-Test obtained sig. (2-tailed) <0.05, namely 0.000, so Ho was rejected and Ha was accepted and it can be concluded that there is an influence of the use of the Think Talk Write type cooperative learning model on mathematical communication skills and is also quite effective to use.